Fiscal rules in the Canadian provinces: Abject failure or qualified success?. (4th October 2016) - Atkinson, Michael M.; Mou, Haizhen; Bruce, Peter
Abstract: Most Canadian provinces have introduced legislation to require politicians of all ideological stripes to meet annual balanced budget (BB) targets. Critics of this type of legislation argue that it is unnecessary, confining, and subject to manipulation. We examine provincial balanced budget legislation before and after the Great Recession and argue that the response of provinces needs to be evaluated taking into account the multiple objectives of fiscal policy and the behavioural changes that the rules introduce, including creative non‐compliance. Rules should be evaluated on their ability to contribute to good fiscal governance rather than on their stringency.